2003
DOI: 10.1152/jn.00817.2002
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Activity Related to the Visual Representation of Arm Movements in the Lateral Cerebellar Cortex

Abstract: Testing the hypothesis that the lateral cerebellum forms a sensory representation of arm movements, we investigated cortical neuronal activity in two monkeys performing visually guided step-tracking movements with a manipulandum. A virtual target and cursor image were viewed co-planar with the manipulandum. In the normal task, manipulandum and cursor moved in the same direction; in the mirror task, the cursor was left-right reversed. In one monkey, 70- and 200-ms time delays were introduced on cursor movement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 55 publications
4
32
1
Order By: Relevance
“…The latency of burst onset times of HMR neurons in the DPN lies between the time range of possible cortical input structures like area 7a where 61% of the HMR neurons precede the movement onset by Ͼ200 ms (Battaglia-Mayer et al, 2007) and motor cortex output that precedes movement initiation by 70 -130 ms (Kakei et al, 1999). On the other hand, it leads those in lobules V and VI of the cerebellum where many neurons fire during movements (Liu et al, 2003), in full accordance with their role as intermediate stages in a pathway linking cerebral cortex and the cerebellum. The difference in burst onset time relative to movement onset between the SR and HMR neurons in the DPN is reminiscent of the differences in the time required to start an eye compared with a hand movement.…”
Section: Discussionmentioning
confidence: 99%
“…The latency of burst onset times of HMR neurons in the DPN lies between the time range of possible cortical input structures like area 7a where 61% of the HMR neurons precede the movement onset by Ͼ200 ms (Battaglia-Mayer et al, 2007) and motor cortex output that precedes movement initiation by 70 -130 ms (Kakei et al, 1999). On the other hand, it leads those in lobules V and VI of the cerebellum where many neurons fire during movements (Liu et al, 2003), in full accordance with their role as intermediate stages in a pathway linking cerebral cortex and the cerebellum. The difference in burst onset time relative to movement onset between the SR and HMR neurons in the DPN is reminiscent of the differences in the time required to start an eye compared with a hand movement.…”
Section: Discussionmentioning
confidence: 99%
“…This idea of multiple predictors is reminiscent of a previous proposal by Miall et al (1993) who suggested that the brain predicts separately the visual and somatosensory consequences of actions. Neurophysiological support for this hypothesis was later provided by Liu et al (2003) who showed that in the cerebellum, distinct neurons code for the visual and somatosensory consequences of limb motion.…”
Section: How Independent Is Grip Force Control From the Adaptation Ofmentioning
confidence: 92%
“…Furthermore, modulation during the cue period cannot account for the modulation during the track period. Both findings suggest that arm movement is the predominant determinant of the simple spike firing for Purkinje cells recorded in this location (Coltz et al, 1999;Liu et al, 2003). However, the modest cue period modulation suggests that Purkinje cells may be participating in preparatory or predictive activity (Marple-Horvat and Stein, 1990;Liu et al, 2003).…”
Section: Cue Periodmentioning
confidence: 92%